PENGARUH MANAJEMEN LABA, GOOD CORPORATE GOVERNANCE DAN BIAYA HUTANG TERHADAP TAX AVOIDANCE - Leni Wulansari; Baiq Fitri Arianti (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This research is based on the action of hotel, tourism and restaurant sub-sector companies in conducting tax avoidance in a legal way. The purpose of this study is to determine the effect of earnings management, good corporate governance, and debt costs on tax avoidance of tourism, hotel and restaurant subsector companies. The population in this study amounted to 48 companies included in the tourism, hotel and restaurant subsector companies during the 2018-2022 period. In this study using a sampling technique, namely purposive sampling and obtained a sample of 25 companies. The analysis method used in this research is panel data regression analysis using eviews software version 12. In this study, the dependent variable is Tax Avoidance (Y) and the independent variables are earnings management (X1), Good Corporate Governance (X2) proxied by Managerial Ownership and Debt Cost (X3). The results stated that earnings management (X1), Good Corporate Governance (X2) which is proxied by Managerial Ownership and Debt Costs (X3) have a simultaneous and significant effect on Tax Avoidance (Y). Partially, Earnings Management has a negative effect on Tax Avoidance (Y), Good Corporate Governance (X2) has no effect on Tax Avoidance (Y), and Debt Costs (X3) have no effect on Tax Avoidance (Y).